Evaluasi Dampak Program Dapur Sehat Atasi Stunting Melalui Model CIPP pada Peserta Aktif Posyandu di Kampung KB - Tresnasih, Tasya; Yuliani, Nadya Amalia; Putri, Amelia Fadila; Azzahra, Fatima Rosaphira; Hamdan, Ahmad (Cendekia: Jurnal Pendidikan dan Pemberdayaan Masyarakat, 2024)
Ciamis district has a prevalence of stunting data with an increasing graph even though there is data in 2020 decreasing but, there is an increase in the prevalence of stunting in Ciamis district in 2022 by 2.6% but until now, the Ciamis district government has continuously tried to emphasize the stunting rate in each village. One of the programs that support the reduction in stunting rates is the DARMAZI (Nutritious Food Kitchen) program. This program has been running well and in accordance with established procedures. The DARMAZI (Nutritious Food Kitchen) program process is divided into three case locations, including: cijenjing, sadananya, and ciamis sub-districts. In the implementation of this program we used the CIPP evaluation model. Evaluation of the CIPP Model in the Healthy Kitchen Overcoming Stunting (DASHAT) Program has an impact on the community, especially on mothers who are active participants in posyandu in KB Village such as increasing knowledge and understanding of supplementary feeding as an effort to reduce stunting rates and improve participants' skills in processing nutritious and healthy food as additional food for toddlers and to increase the skills of participants' mothers to use local food ingredients around the neighborhood.